Screening for phenylketonuria in a totalitarian state. - Kalaydjieva, L (1992)
Living under a totalitarian regime has many effects on the structure, way of thinking, and relations in a society. However, it is the impact on neonatal genetic screening that we discuss in this paper. Genetic screening functions at the interface between health services and society at large. Being involved for over a decade in setting up the Bulgarian PKU screening programme, we have had to deal with ways and attitudes which may be difficult for the western mind to grasp. Yet comprehension is very much needed in the new world we are trying to create.